High-resolution isotopic evidence for a potential Saharan provenance of Greenland glacial dust. Issue 1 (December 2018) - Han, Changhee; Hur, Soon; Han, Yeongcheol; Lee, Khanghyun; Hong, Sungmin; Erhardt, Tobias; Fischer, Hubertus; Svensson, Anders; Steffensen, Jørgen; Vallelonga, Paul
Abstract Dust concentrations in Greenland ice show pronounced glacial/interglacial variations with almost two orders of magnitude increase during the Last Glacial Maximum. Greenland glacial dust was previously sourced to two East Asian deserts: the Taklimakan and Gobi deserts. Here we report the first high-resolution Pb and Sr isotopic evidence for a significant Saharan dust influence in Greenland during the last glacial period, back to ~31 kyr ago, from the Greenland NEEM ice core. We find that during Greenland Stadials 3–5.1 (~31 to 23 kyr ago), the primary dust provenance was East Asia, as previously proposed. Subsequently, the Saharan isotopic signals emerge during Greenland Stadials 2.1a–2.1c (~22.6 to 14.7 kyr ago) and from the late Bølling-Allerød to the Younger Dryas periods (~13.6 to 12 kyr ago), coincident with increased aridity in the Sahara and efficient northward transport of dust during these cold periods. A mixing isotopic model proposes the Sahara as an important source, accounting for contribution to Greenland glacial dust of up to 50%, particularly during Greenland Stadial 2.1b and the late Bølling-Allerød to the Younger Dryas periods. Our findings provide new insights into climate-related dust provenance changes and essential paleoclimatic constraints on dust-climate feedbacks in northern high latitudes.